Efeito do Harpagophytum procumbens sobre parâmetros de estresse oxidativo e a viabilidade celular in vitro - Schaffer, Larissa Finger (2013)
Harpagophytum procumbens, known as devil's claw, is an African plant with numerous therapeutic effects, among which stands out for its powerful anti-inflammatory action, but the mechanism by which exerts its effect is not well elucidated. It is known that reactive oxygen species and / or nitrogen are generated in acute and chronic inflammatory diseases causing high cytotoxicity that leads to tissue damage. Substances with antioxidant action can contribute to control and/or treat the inflammatory process.Thus, the goal of this study was to evaluate the effect of the infusion, the crude extract and fractions of H. procumbens on lipid peroxidation induced by different pro-oxidant agents (Iron or sodium nitroprusside). Furthermore, the effects of the ethyl acetate fraction was also tested on the antioxidant defenses (catalase activity and thiol protein and non-protein levels) and on cellular damage (cerebral cortex slices) induced by different pro-oxidant agents. All extracts prevented lipid peroxidation induced by Fe2+ and sodium nitroprusside. Ethyl acetate fraction of H. procumbens showed great power to protect against lipid peroxidation, prevention of cellular death, and shows ability to maintain the thiol levels and catalase activity in basal standarts. In conclusion, this study demonstrates that one of the possible mechanisms for therapeutic action presented by H. procumbens may be related to its antioxidant action, being was able to protect against oxidative stress and loss of cell viability. Once the relationship of inflammation process with oxidative stress is already well described in the literature, the antioxidant effect can also be found here related to potent anti-inflammatory effect exerted by H. procumbens. However more studies are needed on the mechanisms by which H. procumbens exerts its therapeutic effects.